A Comparison of Emotional-Behavioral Problems of siblings at the Age Range of 3-9 Years Old of Children with Autism and Down syndrome - pourbagheri, nahid; mirzakhani, navid; Akbarzadeh Baghban, alireza (Iranian Journal of Child Neurology, 2018)
Abstract Objectives: Children’s emotional-behavioral problems will have a huge impact on their future. It seems such problems are more seen in the siblings of children with special needs. The present study sought to compare emotional-behavioral problems in the healthy siblings of autistic children with the healthy siblings of children with Down syndrome in order to identify such children in Iran. Materials & Methods: This descriptive study was carried out on 174 healthy children aged between 3 and 9 years old among whom 58 cases had autistic siblings, 58 cases had siblings with Down syndrome, and 58 cases had typically development siblings. The participants were selected using convenience sampling technique. All volunteer parents filled in SDQ Questionnaire. The study results were calculated using independent sample t-test, two-way ANOVA, and Tukey post hoc test by SPSS Software V.21. Results: The mean overall score of Strengths and Difficulties questionnaire was reported as 17.98±6.19 in the autism group, 11.01±6.56 in the Down syndrome group and 4.43±4.34 in the healthy group so that there was a significant difference among autism, Down syndrome and healthy groups. In the group of siblings with Down syndrome, the problems were significantly more in the age range of 3 to 7 years old (p <0.05). However, no significant difference was observed in the scores of males and females (p> 0.05). Conclusions: Siblings with autism or Down syndrome can have especial psychological effects on healthy children in families in the way that such effect will be more with autistic children. Therefore, formulating beneficial strategies for their parents is useful to prevent emotional- behavioral problems.